Exploring the Mechanism of Action of Canmei Formula Against Colorectal Adenoma Through Multi-Omics Technique - Guo, Cui; Liu, Xiaoqiang; Xu, Yimin; Han, Xinyue; Xie, Runnan; Meng, Xiangxue; Li, Yuan; Chen, Tongyu; Cheng, Zhihong; Fu, Xiaoling (Frontiers in Cell and Developmental Biology, 2021)
Background: Canmei formula (CMF) is a traditional Chinese medicine compound with definite effect on the prevention and treatment of colorectal adenoma (CRA). It can prevent the transformation of intestinal inflammation to cancer. This study explored the mechanism of action of CMF in anti-CRA using multi-omics techniques. Method: Mice were randomly divided into 4 groups: blank group (Control), high-fat diet (HFD) + AOM/DSS colorectal adenoma model (ADH) groups, Canmei formula treatment group (ADH-CMF) and sulfasalazine treatment group (Sul). Except for the blank group, ADH model was established in the other 3 groups by intraperitoneal injection with AOM reagent, and then mice was given 2.5%DSS in free drinking water and high-fat diet. The mice in the blank group and ADH group were intragastrically perfused with normal saline, and the mice in the other 2 groups were treated with corresponding drugs for 20 weeks. During this period, the changes of physical signs of mice in each group were observed. The differentially expressed genes and proteins in the Control group, ADH group and ADH-CMF group were detected by RNA-seq transcriptome sequencing and Tandem Mass Tags (TMT) quantitative proteomics. After the combined analysis and verification. The key targets were analyzed by gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). Moreover, the changes of intestinal flora in the three groups were examined. Results : A total of 2548 differential genes were obtained by transcriptomics analysis, and 45 differential proteins were obtained by proteomics analysis. The results of proteomics data and experimental verification showed that CMF mainly acted on the Phospholysine Phosphohistidine Inorganic Pyrophosphate Phosphatase (LHPP) target. The results of 16S DNA high-throughput sequencing showed that CMF could effectively regulate the abundance of Bifidobacterium, Candidatus_Saccharimonas and Erysipelatoclostridium in the intestinal flora at the genus level. Conclusions : CMF regulates the LHPP target via the PI3K/AKT signaling pathway, and regulates the structure of intestinal flora and the abundance of specific flora, and reverses the disorder of intestinal flora to achieve the role of prevention and treatment of CRA.